Institutional shareholding and the dividend payout policy of Islamic mutual funds: Evidence from international Islamic funds industry - Farrukh Naveed (Borsa İstanbul Review, 2021)
The current research aims to analyze the impact of institutional shareholding on the dividend payout policy of Islamic mutual funds in Pakistan and Malaysia. A sample of 185 Islamic funds, including 85 Pakistani and 100 Malaysian funds, is used for the analysis. The data for the analysis spans nine years, i.e., from 2010 to 2018. The analysis is carried out using the fixed effects regression and dynamic panel system GMM techniques. The results show that institutional ownership has a positive impact on the dividend payout policy of Islamic mutual funds in both countries, which is in line with the assumption of the agency theory. Therefore, asset management firms need to encourage higher institutional ownership to increase dividend payments. In this way, these firms would be able to attract a large number of investors.
Keywords: 330; Dividend payout policy; Institutional shareholding; Islamic mutual funds